THE IMPLEMENTATION DIGITAL-BASED BASIC EDUCATION OF PANCASILA STUDENT PROFILE PROGRAM: AN EFFORT TO STRENGTHEN STUDENTS' CRITICAL AND CREATIVE THINKING - Noptario; Ade Tinofa, Nelva; Khoirotun Nisa, Ani; Abdullah, Faisal; Nazri bin Nordin, Ts. Saiful (UIN Sunan Kalijaga Yogyakarta, 2024)
In the digital era, basic education needs to be revitalized to be renewable and in line with the times. One of the efforts that can be made is to utilize digital technology in learning. The Pancasila student profile program is project-based and can stimulate students to think critically and creatively. However, conventional learning is still found, so it is important to revitalize learning to provide novelty and improve learning. This study aims to reveal revitalization in basic education from conventional to digital-based learning to increase students' critical and creative thinking. This research uses a qualitative research approach with a Field Research research method. Data collection techniques in this study used interviews. Interviews were conducted with the principal, class teachers, and students. Research sources were selected through a purposive sampling technique. The data analysis technique used in this study uses thematic analysis theory to understand the data, compile codes, and look for themes. The location of this research is SDN Wijilan Kulonprogo Yogyakarta. Revitalization of digital-based learning is carried out by providing training to teachers, preparing supporting facilities and infrastructure and controlling and evaluating. Conventional learning needs to be revitalized because it only focuses on the teacher and makes students less active in learning, so the term digitization in learning emerged. Digitalization in learning can positively impact and make students think critically and creatively because it has advantages such as learning being more varied, students being more active in participating in learning, helping students improve their technological skills, and diverse learning resources. Teachers in the Pancasila student profile program strongly feel these advantages, as they can make students think critically and creatively.